2022
DOI: 10.1063/5.0122247
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical framework bridging classical and quantum mechanics for the dynamics of cryogenic liquid helium-4 using smoothed-particle hydrodynamics

Abstract: Our recent study suggested that a fully classical mechanical approximation of the two-fluid model of superfluid helium-4 based on smoothed-particle hydrodynamics (SPH) is equivalent to solving a many-body quantum mechanical equation under specific conditions. This study further verifies the existence of this equivalence. First, we derived the SPH form of the motion equation for the superfluid component of the two-fluid model, i.e., the motion equation driven by the chemical potential gradient obtained using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…In addition, our recent study showed that the SPH simulation of the angular momentum-conserving two-fluid model incorporating vortex dynamics reproduces vortex lattices [13]. Our another study provided a theory that the equation of motion for inviscid fluids in the two-fluid model becomes equal to the quantum hydrodynamic equation derived from the GP equation under specific conditions in SPH form [6]. Therefore, describing the GP equation in SPH form may help to find some connection with these studies.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…In addition, our recent study showed that the SPH simulation of the angular momentum-conserving two-fluid model incorporating vortex dynamics reproduces vortex lattices [13]. Our another study provided a theory that the equation of motion for inviscid fluids in the two-fluid model becomes equal to the quantum hydrodynamic equation derived from the GP equation under specific conditions in SPH form [6]. Therefore, describing the GP equation in SPH form may help to find some connection with these studies.…”
Section: Introductionmentioning
confidence: 70%
“…Because the GP equation is a nonlinear Schro dinger equation of interacting bosons, its Hamiltonian is described as a many-body interaction system [4][5][6]. Therefore, compared to other Euler methods such as finite element (FE) [7][8][9] and finite difference (FD) [10][11][12] methods, the mechanical picture of the SPH scheme is closer to real BEC physics; we can describe the GP equations as a many-body interaction system in SPH.…”
Section: Introductionmentioning
confidence: 99%